The Impact of Hydration on Metabolic Outcomes: From Arginine-Vasopressin Signaling to Clinical Implications - Andrijana Koceva; Andrej Janež; Mojca Jensterle (Medicina)
Arginine-vasopressin peptide (AVP) plays a critical role in water balance and osmoregulation. However, emerging evidence suggests that AVP’s actions may expand beyond its traditional role, significantly influencing metabolic regulation, including glucose homeostasis, insulin sensitivity, lipid metabolism and energy balance. Elevated AVP levels are seen in various metabolic conditions, such as insulin resistance, metabolic syndrome, type 2 diabetes (T2D) and obesity, further highlighting its potential role as a metabolic regulator. As AVP levels are regulated by hydration status, studies have proposed that chronic hypohydration and persistently elevated AVP levels may contribute to metabolic dysfunction, where increased hydration and therefore AVP suppression may lead to potential metabolic improvements. By analyzing data from animal studies, human observational research and interventional trials, this review evaluates the current evidence on the potential causal relationships and impact of AVP on metabolic regulation, as well as exploring the role of hydration in AVP-mediated metabolic outcomes.